The Study of the Parameters of Amplitude-Modulated Sweep Signal of the Shock Vibration Source of Seismic Signals - Moyzes [Moises] B. B. Boris Borisovich (2023, 2023)
The purpose of the research is to document the development process of a low-weight seismic shock vibration sensor with an amplitude-modulated sweep signal, and which possess good signal-to-noise ratio characteristics. The development of such a source of seismic signals will make it possible to study the interior of the Earth in difficult terrain geographic regions. To achieve this goal, the designs of seismic sources were analyzed and their “positive” design features were defined; the effect of different law of amplitude-modulated sweep signal on the degree of compactness of the autocorrelation function was studied; theoretical studies were carried out on the oscillatory system seismic source behavior with the simultaneous impact of a force pulse from a falling load, which forms the pressing force of the base plate and a sweep signal from the oscillation generator; the experimental studies were carried out on a vibration bench which is a physical model of the source; the possibility of excitation of a sweep signal with amplitude modulation was studied; the parameters of the excitation process and the operation modes of the vibration mechanism for the formation of a useful vibration load are recommended